An Overground Robotic Gait Training Program for People With Multiple Sclerosis: A Protocol for a Randomized Clinical Trial - Berriozabalgoitia, Rakel; Sanz, Begoña; Fraile-Bermúdez, Ana Belén; Otxoa, Erika; Yeregui, Izaskun; Bidaurrazaga-Letona, Iraia; Duñabeitia, Iratxe; Antigüedad, Alfredo; Domercq, Maria; Irazusta, Jon; Rodriguez-Larrad, Ana (Frontiers in Medicine, 2020)
Maintaining the ability to walk is one of the significant challenges in people with multiple sclerosis (MS) for keeping a good quality of life as the disease and the aging process progresses. Overground robotic (OR) wearable exoskeletons are promising tools for gait rehabilitation, but currently there is no evidence of their clinical effects on patients with MS. The present study aims to determine the effects of the addition of an OR intervention to the conventional rehabilitation program on gait speed in people with MS and moderate to severe walking disabilities and ascertain if benefits are maintained over a follow-up period of 3 months. This randomized controlled trial will include 36 participants with MS. Inclusion criteria are: older than 18 years, definitive diagnosis of MS, 4.5-7 points on the EDSS (Expanded Disability Status Scale), and needing one or two canes or crutches for walking outdoors. Subjects in the control group will receive conventional physiotherapy sessions at ADEMBI (Asociación de Esclerosis Múltiple de Bizkaia) provided to control spasticity, maintain articular range and exercise balance. Subjects in the intervention group will receive the same physiotherapy but also participate in a progressive OR gait training program assisted by the EksoTM exoskeleton. The program consists of twice a week individually supervised sessions in two setting modalities: PreGait and ProStepPlus. The training parameters (duration, speed, cadence, length of steps) will be set during the first session and the progression and intensity of the intervention will be adapted to the tolerance of each participant. The primary outcome of this study is gait speed. Secondary outcomes will include physical and cognitive performance tests, clinical, fatigue and quality of life assessments, and changes in the plasma levels of inflammatory cytokines. The present trial is the first analyzing the effectiveness of an OR intervention for gait training in patients with MS. It will help clarify the applicability of robotic technologies to clinical practice, extending the functionality and quality of life of people with MS to face a successful aging process. (ACTRN12619000014156; https://anzctr.org.au/Trial/Registration/TrialReview.aspx?id=376548).